P-019 Interval angioarchitectural evolution of brain arteriovenous malformations following rupture. (22nd July 2018) - Jin, H; Lenck, S; Agid, R; Tymianski, M; Krings, T; Radovanovic, I; Pereira, V Mendes
Abstract : This study evaluates modifications in the angioarchitecture of bAVM between acute and delayed cerebral angiograms (DSAs) after haemorrhage without early treatment. Methods: This is a retrospective study of a prospective institutional bAVM database. We included all patients with ruptured bAVMs who had DSA in both acute and delayed phases with no interval treatment of their bAVM from January 2000 to April 2017. We evaluated the existence or absence of angioarchitectural changes. Demographics, radiological characteristics of hemorrhages and angioarchitectural features of the bAVM of the two patients' groups were analyzed. Univariate and multivariate logistic analysis were performed to identify predictors of angioarchitectural modifications. Results: A total of 42 patients were included in our series. Seventeen (40.5%) patients had angioarchitectural changes including bAVM only visible on the delayed DSA (n=8), spontaneous thrombosis of the AVM (n=3), or alteration of the size or the opacification of the nidus (n=6). The factors associated with angioarchitectural changes were a small nidus size (3.8±7.9 vs 6.1±9.5 ml, p=0.046), a superficial location (94.1% vs 5.9%, p=0.016), and a single superficial draining vein (58.8% vs 24.0%, p=0.029). Conclusions: Angioarchitectural changes can be seen in 40% of ruptured bAVM between the acute and delayed-phase DSA. A small nidus size, a superficial location and a single superficial draining vein were statistically associated with the occurrence of angioarchitectural changes. These changes included either enlargement or spontaneous occlusion of the bAVM, as well as subsequent diagnosis of a bAVM following an initial negative DSA. Disclosures: H. Jin: None. S. Lenck: None. R. Agid: None. M. Tymianski: None. T. Krings: None. I. Radovanovic: None. V. Mendes Pereira: None.